Cancer patient preferences for traditional Chinese medicine treatment: a discrete choice experiment study - Jiao Zhang; Lihua Li; Huinan Xi; Qi Wang; Fan Jiang; Xin Sun; Xuebin Qiao; Aijun Xu (BMC Complementary Medicine and Therapies)
Abstract Background Patient preferences have gradually been incorporated into decisions about cancer treatment regimens over recent years. Meanwhile, the efficacy of traditional Chinese medicine (TCM) in cancer-related treatments has been recognized. This study aimed to estimate the specific preferences of cancer patients for TCM treatment regimens to inform the clinical decision-making process for health promotion. Methods This cross-sectional investigation employed a discrete choice experiment (DCE) methodology to assess TCM treatment regimens preferences among cancer patients. The DCE systematically elicits participants’ preferences through the sequential presentation of hypothetical clinical scenarios with varying combinations of therapeutic attributes, with subsequent data analysis conducted using mixed logit models. We applied this methodology to examine cancer patient preferences regarding different TCM treatment regimens. Additionally, a subgroup analysis of sex groups was conducted to identify potential preference variations across demographic groups. Results In total, 728 participants completed the questionnaire and passed the consistency test. Control rate of disease, gastrointestinal adverse effects, mode of administration, treatment duration, quality of life, and monthly out-of-pocket cost had a significant impact on the TCM treatment preference of the participating cancer patients. Preferences almost remained consistent irrespective of the participants’ sex. Conclusions Differences in treatment have an impact on the preferences of TCM treatment in cancer patients. Cancer patients' preferences related to the control rate of disease and quality of life should be prioritized and considered in TCM treatment decision-making.